Delayed results of treatment of paracoccidioidomycosis with amphotericin B plus sulfamides versus amphotericin B alone - Dillon, Neuza Lima [UNESP]; Sampaio, Sebastião A. P.; Habermann, Marta Cassoni [UNESP]; Marques, Silvio Alencar [UNESP]; Lastoria, Joel Carlos [UNESP]; Stolf, Hamilton Ometto [UNESP]; Selva, Nilson Camargo de Andrade [UNESP]; Curi, Paulo Roberto [UNESP] (Instituto de Medicina Tropical, 1986)
Os Autores avaliam tardiamente dois grupos de doentes de paracoccidioidomicose. Ambos foram tratados com anfotericina B, tendo um deles feito tratamento de manutenção com sulfamídicos. Através de análises estatísticas comprovam a maior eficácia do tratamento, quando se faz a manutenção com sulfamídicos.

A delayed evaluation of two groups of patients with paracoccidioidomycosis was carried out. Both groups were treated with amphotericin B, but one of them was submitted to maintenance treatment with sulfonamides. Statistical analysis showed that treatment is more effective when patients are maintained with sulfonamide drugs.
Resultados tardios do tratamento da paracoccidioidomicose com anfotericina B mais sulfamídicos versus anfotericina B isoladamente
Keywords: Human paracoccidioidomycosis; Treatment with amphotericin and sulfamides